(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
India is a vast sub-continent consisting of numerous villages with a population predominantly devoted to agricultural pursuits. In this agricultural society, each village became a self-sufficient unit and the exchange of goods and services was conducted larger on a barter basis. In view of this small self contained unit, there was very limited scope for investment of large capital and modem life insurance meant accumulation of funds and their investment on a long term basis. The influence of Islam too was against usury. During 19th century the Indians were generally unaware of the advantages and utility of life insurance but there was a widespread superstition that to insure one’s life was to court death. In local languages of the country life insurance was often described as Registration for Death.